Analisis Dinamika Keadilan Lingkungan dan Pengelolaan Sumber Daya Alam: Studi Kasus Pencapaian Hak Tanah Masyarakat Desa Wadas terhadap Rencana Pembangunan Bendungan Bener - Ramadhan, Arief Fadillah; Hafiz, Achmad; Nabila, An Nissa; Ronggur, Aryo; Dewinta, Chairunnisa (Pusat Riset dan Inovasi Nasional, 2024)
In the context of environmental law enforcement, justice is a crucial element. Recognizing the importance of justice in the context of the environment and natural resource management is expected to raise awareness about environmental care and sustainable preservation efforts. The management of natural resources plays a key role in shaping the development of human societies. Land resources hold significant importance for human survival, as they are used in various human activities such as agriculture, industry, housing, transportation networks, recreation, and environmental conservation for scientific purposes. However, many conflicts arise concerning land, with concrete examples such as land disputes. Efforts to protect the environment have been made through various means, including community participation, stakeholder involvement, regulation, national and international agreements, legislation, and law enforcement. Additionally, scientific and technological approaches, as well as technical programs, have also been employed in environmental protection efforts. Nevertheless, environmental issues have not yet been fully effectively addressed. An example is the case of the Land Rights Achievement of the Wadas Village Community in relation to the Bener Dam Development Plan. This research has the potential to be used as a dynamic analysis of environmental justice and natural resource management.